2014
DOI: 10.5091/plecevo.2015.951
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of leaf trait relationships in coastal dunes in southern Spain

Abstract: Background and aims -Coastal dunes of southern Spain are an original Mediterranean ecosystem, hotspot of biodiversity, insufficiently studied under the functional ecology. We explore co-variation patterns among leaf traits (size, specific leaf area (SLA), nutrient concentrations (N, P, K…), deciduousness and leaf consistence), and growth form in 78 native coastal dune species. Methods -Three coastal dunes of contrasting climatic conditions were sampled and differentiated between fixed and mobile dunes. Species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(87 reference statements)
0
3
2
Order By: Relevance
“…Reduced SLA is associated with stress tolerance and promotes nutrient retention, the reduction of water loss, and lowered susceptibility to desiccation ( Navarro and Hidalgo-Triana, 2021 ). Compared with SLA of plants in other Mediterranean shrubland ecosystems, including coastal dunes in southern Spain ( Rodríguez-Gallego et al., 2015 ), Mediterranean shrublands in Andalusia ( Navarro and Hidalgo-Triana, 2021 ) and Iberian Cistus shrublands ( Pérez Latorre and Cabezudo, 2002 ), the values for SLA detected in our study were small. Although Harrison et al.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Reduced SLA is associated with stress tolerance and promotes nutrient retention, the reduction of water loss, and lowered susceptibility to desiccation ( Navarro and Hidalgo-Triana, 2021 ). Compared with SLA of plants in other Mediterranean shrubland ecosystems, including coastal dunes in southern Spain ( Rodríguez-Gallego et al., 2015 ), Mediterranean shrublands in Andalusia ( Navarro and Hidalgo-Triana, 2021 ) and Iberian Cistus shrublands ( Pérez Latorre and Cabezudo, 2002 ), the values for SLA detected in our study were small. Although Harrison et al.…”
Section: Discussioncontrasting
confidence: 87%
“…Reduced SLA is associated with stress tolerance and promotes nutrient retention, the reduction of water loss, and lowered susceptibility to desiccation (Navarro and Hidalgo-Triana, 2021). Compared with SLA of plants in other Mediterranean shrubland ecosystems, including coastal dunes in southern Spain (Rodrıǵuez-Gallego et al, 2015), Mediterranean shrublands in Andalusia (Navarro and Hidalgo-Triana, 2021) and Iberian Cistus shrublands (Peŕez Latorre and Cabezudo, 2002), the values for SLA detected in our study were small. Although Harrison et al (2017) have demonstrated that serpentine plants have a lower SLA than non-serpentine plants, we did not find a significant effect of the serpentine affinity category, perhaps because we sampled plants inhabiting serpentine ecosystems with different degrees of affinity, whereas Harrison et al (2017) studied both serpentine and nonserpentine ecosystems.…”
Section: Variation and Trends In Plant Ftscontrasting
confidence: 62%
“…We obtained trait data from online databases (Kleyer et al, 2008;Aguiar et al, 2013;Tavşanoğlu and Pausas, 2018;Kattge et al, 2020;Royal Botanic Gardens Kew, 2020) and complemented it with information from the literature and floras (Castroviejo, 1986(Castroviejo, -2012Mediavilla and Escudero, 2003;Cerabolini et al, 2010;Plantureux and Amiaud, 2010;Milla and Reich, 2011;Bejarano et al, 2012;Domínguez et al, 2012;Pierce et al, 2012;Rodríguez-Gallego et al, 2015;Bejarano et al, 2016;de la Riva et al, 2016;Aguiar et al, 2018;Pan et al, 2020). Trait data from regional databases and studies, focused on the Mediterranean or Europe, were favoured in trait search when possible.…”
Section: Trait Datamentioning
confidence: 99%
“…Trait data were obtained mainly from online databases, including the TRY Plant Trait Database (Kattge et al, 2020), FLOWBASE-A Riparian Plant Traitbase (Aguiar et al, 2013), BROT 2.0 Functional Trait Database for Mediterranean Basin Plants (Tavşanoğlu & Pausas, 2018), LEDA Traitbase (Kleyer et al, 2008), and Seed Information Database-SID (Royal Botanic Gardens Kew, 2020), and complemented with information from the literature and floras (Bejarano et al, 2016;Castroviejo, 1986Castroviejo, -2012Cerabolini et al, 2010;Mediavilla & Escudero, 2003;Rodríguez-Gallego et al, 2015). Trait data from regional databases and studies (Mediterranean or European) were privileged in trait search when possible.…”
Section: Trait Datamentioning
confidence: 99%